084 A rare case of neurosyphilis imitating limbic encephalitis. Issue 12 (14th November 2019) - Minton, Thomas; Giavasi, Christina; Gamoudi, Donia
Abstract : Neurosyphilis refers to the infection of the central nervous system (CNS) with the Spirochete bacterium Treponema Pallidum (T.Pallidum). Due to the heterogeneity of clinical manifestations of neurosyphilis diagnosis can often be difficult. Here we describe the case of 37 year old heterosexual male, presenting with a 6 month history of recurrent episodes of expressive dysphasia, right upper limb paraesthesia and weakness, photopsia and headaches. Magnetic resonance imaging demonstrated bilateral temporal lobe signal abnormalities consistent with a viral or limbic encephalitis. Serum Treponema screening and CSF VDRL were both positive, consistent with a diagnosis of neurosyphilis. He was successfully treated with antibiotics, but has been left with left hippocampal sclerosis. The transient neurological symptoms were felt to be epileptic phenomena and his symptoms improved significantly with Lamotrigine. This case highlights the importance of early consideration of neurosyphilis in the differential for limbic or viral encephalitis.